Evolution of glacial lakes in Southern Patagonian Icefield between 1986 and 2023 - Carrión, Daniela; Berkhoff, Jorge; Loriaux, Thomas; Wilson, Ryan; Rada, Camilo; Ugalde, Felipe; Bravo, Claudio (Frontiers in Earth Science, 2025)
This article presents satellite-based monitoring of glacial lakes located in the vicinity of the Southern Patagonian Icefield (SPI) between 1986 and 2023, with a focus on year-by-year changes between 2015 and 2023. Glacial lakes in this region are of importance as their growth represents an indirect response to climate change and has implications for local ecosystems, tourism, and recreation. The growth of glacial lakes also has implications regarding the potential generation of Glacial Lake Outburst Floods (GLOFs), and this study therefore enables a better understanding of the evolution of the GLOF hazard associated with the SPI. Using a total of 93 Landsat and Sentinel-2 satellite images, glacial lakes were mapped with the aid of the Normalized Difference Water Index (NDWI) and visual analysis and differentiated into three distinct types (moraine-dammed, bedrock-dammed, and ice-dammed). In addition, the volume of glacial lake water was estimated using an empirical area-volume scaling approach. Our results show that the number, area and volume of glacial lakes around the SPI have increased by 34%, 29% and 31%, respectively, between 1986 and 2023. The most recent inventory (2023) identified 313 lakes with a total area of 639.09 km2 and a total volume of 34.84 km3. Of the lakes identified in 2023, moraine-dammed lakes accounted for the largest portion (165), followed by bedrock-dammed lakes (76) and ice-dammed lakes (72). A temporal analysis of the lakes by type revealed that (1) bedrock-dammed lakes exhibited the greatest stability, (2) moraine-dammed lakes showed the most significant growth in number and total area, with the number of lakes stagnating after 2016, and (3) ice-dammed lakes were the most dynamic and variable. Overall, our results highlight that the glacial lakes of the SPI are undergoing complex changes in response to glacial decline, and continued monitoring is necessary to quantify their impact on future glacier mass balance, GLOF hazard and risk, ecological change and the broader socio-economics of the region.